Análisis del estrés térmico en los trabajadores de la empresa “APRODEMAG”. - Jiménez Riera, Jonathan Maximiliano (2019)
The purpose of this study was to propose the use of a manual for works at low temperatures (cold) in APRODEMAG. In order to guarantee the development of the manual; the thermal conditions to which the workers are exposed were previously evaluated during their normal working hours, and this was compared with the workload table of Executive Decree 2393, heat stress by heat, to know the TGBH index, a measurement instrument was used. Through it the values obtained did not exceed those established in the chart. However, the risks that exist due to exposure to low temperatures are latent, such as the lack of acclimatization, age, gender and use of PPE suitable for cold environments which should be controlled immediately. In addition, the initial situation of the company was analyzed through the support of the minimum plan for prevention of occupational risks and the requirements of Good Preventive Practices. Based on the initial situation of the company a 56% complies with the stipulated in the official register, 39% does not comply and finally 5% does not apply. With this data the proposal of improvement regarding the implementation of the manual was elaborated. The study was proposed as a non-experimental research and a field modality was adopted by applying a literature review according to the needs of the company, where it was possible to identify the risks that may exist. Therefore, the preventive and corrective measures along the productive process were established